KUALITAS HIDUP PADA PASIEN ULKUS DIABETIK DI RUANGAN PERAWATAN RUMAH SAKIT AMINAH - Novis Desrian Afiko; Hendry Kiswanto Mendrofa (KOLONI, 2022)
Diabetic ulcers are open sores on the skin surface due to complications of macroangiopathy, which is a wound in a patient that is often not felt, and can develop into an infection caused by aerobic or anaerobic bacteria. Quality of life can be viewed from a subjective and objective perspective. The subjective aspect is feeling good and satisfied with everything in general, while objectively is the fulfillment of the demands of material welfare, social status and socio-cultural physical perfection. The purpose of this study is to describe the quality of life of patients with diabetic ulcers in the Aminah Hospital Tangerang ward in 2021. The design of this study is descriptive quantitative exploratory in nature. done by visiting directly to the Aminah Hospital Treatment Room. The population in this study were 24 patients with diabetic ulcers in the Aminah Hospital ward during April. In this study, the instrument used was the whoqol-bref quality of life questionnaire. The research method used was descriptive quantitative. 1 obtained the mean or average value of 24 respondents with diabetic ulcers of (45.54%), then for domain 2 about psychological health the mean / average value with 24 responses who experienced diabetic ulcers was 42.38% where this score still in the good category, for domain 3 about social relations which includes aspects of social relations, sexual relations, and social support. Of the 3 aspects that have been integrated into domain 3, the average value is (40.29%) and finally in domain 4, the average value is obtained (44.29%). Keywords: Quality of Life, Diabetic Ulcer